Preventive HIPEC in combination with perioperative FLOT versus FLOT alone for resectable diffuse type gastric and gastroesophageal junction type II/III adenocarcinoma – the phase III “PREVENT”- (FLOT9) trial of the AIO /CAOGI /ACO - Thorsten O. Götze; Pompiliu Piso; Sylvie Lorenzen; Ulli S. Bankstahl; Claudia Pauligk; Moustafa Elshafei; Giuseppe Amato; Daniel Reim; Wolf O. Bechstein; Alfred Königsrainer; Stefan P. Mönig; Beate Rau; et al. (BMC Cancer, 2021)
Abstract Background The main reason for treatment failure after curative surgical resection of gastric cancer is intra-abdominal spread, with 40–50% peritoneal seeding as primary localization of recurrence. Peritoneal relapse is seen in 60–70% of tumors of diffuse type, compared to only 20–30% of intestinal type. Hyperthermic IntraPEritoneal Chemoperfusion (HIPEC) is an increasingly used therapy method for patients with peritoneal metastases. The preventive use of HIPEC could represent an elegant approach for patients (pts) before macroscopic peritoneal seeding, since pts. with operable disease are fit and may have potential risk of microscopic involvement, thus having a theoretical chance of cure with HIPEC even without the need for cytoreduction. No results from a PCRT from the Western hemisphere have yet been published. Methods This is a multicenter, randomized, controlled, open-label study including a total of 200 pts. with localized and locally advanced diffuse or mixed type (Laurens’s classification) adenocarcinoma of the stomach and Type II/III GEJ. All enrolled pts. will have received 3–6 pre-operative cycles of biweekly FLOT (Docetaxel 50 mg/m2; Oxaliplatin 85 mg/m2; Leucovorin 200 mg/m2; 5-FU 2600 mg/m2, q2wk). Pts will be randomized 1:1 to receive surgery only and postoperative FLOT (control arm) or surgery + intraoperative HIPEC (cisplatin 75 mg/m2 solution administered at a temperature of 42 °C for 90 min) and postoperative FLOT (experimental arm). Surgery is carried out as gastrectomy or transhiatal extended gastrectomy. Primary endpoint is PFS/DFS, major secondary endpoints are OS, rate of pts. with peritoneal relapse at 2 and 3 years, perioperative morbidity/mortality and quality of life. The trial starts with a safety run-in phase. After 20 pts. had curatively intended resection in Arm B, an interim safety analysis is performed. Recruitment has already started and first patient in was on January 18th, 2021. Discussion If the PREVENT concept proves to be effective, this could potentially lead to a new standard of therapy. On the contrary, if the outcome is negative, pts. with gastric cancer and no peritoneal involvement will not be treated with HIPEC during surgery. Trial registration The study is registered on June 25th, 2020 under ClinicalTrials.gov Identifier: NCT04447352 ; EudraCT: 2017-003832-35 .